Teologi Islam rasional : apresiasi terhadap wacana dan praksis Harun Nasution - Halim, Abdul, 1967- (Jakarta : Ciputat Press, 2001)
Effort and thought of Harun Nasution on development of Islamic studies in the curriculum of Islamic universities in Indonesia; collection of articles
Keywords: Nasution, Harun, -- 1919-; Islam and reason; Intellect -- Religious aspects -- Islam; Islamic education -- Indonesia -- Curricula